Predictive factors for recurrent suicide attempts: Evidence from the ACTION‐J study. Issue 2 (12th April 2022) - Tachikawa, Hirokazu; Takahashi, Sho; Nemoto, Kiyotaka; Yonemoto, Naohiro; Oda, Hiroyuki; Miyake, Yasufumi; Hirayasu, Yoshio; Arai, Tetsuaki; Kawanishi, Chiaki
Abstract: Aim: Risk factors for attempted suicide have been widely studied. However, there is limited evidence on predictive factors for suicide reattempts. We aimed to identify these in suicide attempters admitted to emergency departments. Methods: This is the second analysis from a randomized controlled multicenter trial, ACTION‐J. Patient characteristics were extracted from baseline demographic data and clinical data of participants. Predictive factors for a recurrent suicide attempt in each gender were examined using Cox proportional hazards regression analysis. Dependent variables were months from trial entry to the first reattempt. Independent variables were characteristics regarded as potential predictive factors. Results: The study included 914 adults (400 men and 514 women). A visit to a psychiatrist within a month of the suicide attempt was significantly associated with reattempts in men (hazard ratio [HR] 2.49, 95% confidence interval [CI] 1.21–5.25). Substance‐related disorders (HR 3.65, 95% CI 1.16–7.9.60), drinking alcohol less than once per month (HR 0.42, 95% CI 0.17–0.88), previous suicide attempts (HR 2.28, 95% CI 1.40–3.87), and taking a drug overdose for the first suicide attempt (HR 1.82, 95% CI 1.14–3.01) were significantly associated with reattempts in women. Conclusion: Our data highlight the importance of visits to a psychiatrist a short time before the first suicide attempt in men and substance‐related disorder, previous suicide attempts, and drug overdose in the first suicide attempt in women as predictive factors for future suicide reattempts. Abstract : We aimed to identify predictive factors for suicide reattempts in suicide attempters admitted to emergency departments as the second analysis of the ACTION‐J study. We found that visits to a psychiatrist a short time before the first suicide attempt in men and substance‐related disorder, previous suicide attempts, and drug overdose in the first suicide attempt in women as predictive factors for future suicide reattempts.